Exposure to Interbank Investment and Financing Risk by Islamic Banks: a Dynamic Panel Analysis of Malaysia - Mohammad Taqiuddin Mohamad; Ahmad Azam Sulaiman; Khairul Hamimah Mohammad Jodi; Nazri Muslim (2019)
The government of Malaysia has developed an Islamic Interbank Money Market (IIMM) since January 1994 with the objective to facilitate funding for the Islamic banking sector in the country. This platform also enables Islamic banks to obtain Shariah-compliant funds from other Islamic banks. This article examines the effects of interbank investment and financing risk on the financing decisions of Malaysia’s Islamic bank between 1994-2015. The financing decisions are used as financing measures to determine the effect of investing in the interbank market and financing risk indicators on financing. Research methodology are the descriptive, correlation and dynamic panel analysis results are derived with the help of Limdep 9.0 software. The study found a negative relationship between the interbank investment variable with the financing decisions of Islamic banks. This reflects that an increase in interbank investment leads Islamic banks to reduce their level of financing. These findings prove the investment activities between Islamic banks had a “substitution effect” and decreased their capability of financing because of their tendency to maintain liquidity. Islamic banks are confident that they will generate higher profits in the coming financial year. The economic conditions of Malaysia do not influence Islamic banks’ financing decisions, whereas Islamic banks in this study are more dependent on the balance sheet indicators. (Abstract by authors)